Utilization of Online Referral for National Health Insurance Patient Services in Indonesia: A Scoping Review - Luluk Andani; Sutopo Patriajati; Farid Agushybana (Jurnal Penelitian Pendidikan IPA, 2023)
The evolution of the outpatient referral system for BPJSK participants has transitioned from a manual-based system to an online-based approach. The present discourse examines the use of online referrals in patient care under NHI programme in Indonesia. The literature search conducted in this systematic review adheres to the PRISMA methodology and utilises the Google Scholar and PubMed databases. Using online referral in the context of NHI patients is a topic of interest. A total of six papers underwent a systematic evaluation. The assessment of the utilization of online referrals was conducted by evaluating patient satisfaction and the effectiveness of NHI project. The satisfaction of NHI patients concerning time certainty, referral certainty, waiting time, service access, service quality, service process, and service system is influenced by the utilization of online referrals. The practicality of the online referral strategy can be assessed through its impact on programme understanding, targeting precision, goal achievement, and tangible changes. The urgency of online referrals could be more persuasive. In order to enhance the efficiency of waiting time, it is imperative to implement supportive measures, such as the utilization of online queues and streamlining the process of online referrals in primary healthcare settings and hospitals